Validation of questionaire for website usability (QWU) instrument based on experts review - Nur Sukinah, Aziz; Adzhar, Kamaludin (Springer Verlag, 2016)
Nowadays, website is used widely all over a world for medium of communication for information or services and usability principles was implemented in web environment and not for software only. Organization uses website to market their product and services. There are many methods to evaluate the website such as heuristic evaluation, testing, survey and many more. This study is aimed to develop the questionnaire for measuring website in context of usability. The instrument is consist of 9 constructs and 60 item of questionnaire. Content validity by experts is used as one of methodology to validate the instrument. The result shows that from 60 item of instrument, 9 item need to be removed based on experts review. Therefore, it shows some justification for the content validity of items when some items are not focusing to the research target.